Open government partnership as a platform for advancing open education policy - Jan Gondol; Nicole Allen (Open Praxis, 2015)
An exciting new avenue for establishing and expanding national commitments to open education has emerged through the Open Government Partnership (OGP), a multilateral initiative that aims to secure commitments from governments to make their governance more open, accountable and responsive to citizens. In the past, there has not been a strong link between open education and open government, but that has changed in the last year as both the United States and the Slovak Republic adopted commitments to open education in their OGP national action plans. The purpose of this paper is to explore OGP as a strategy for securing national-level commitments to open education in participating countries. We begin by providing background on the OGP, then discuss case studies from the United States and the Slovak Republic, and finally offer recommendations for advocates other countries to consider.